Population genetic assessment of Viburnum japonicum in China using ddRAD-seq - Zhu, Hong; Liu, Juan; Gao, Meirong; Yue, Chunlei; Li, Hepeng (Frontiers in Genetics, 2023)
Viburnum japonicum is a rare plant species and endemic to the coastal region of Eastern Asia with extremely small populations. Within mainland China, this species can be only found in narrow habitats of the northeast coastal islands of Zhejiang Province. However, there are scarce conservation genetic studies on V. japonicum, which has limited the effective conservation and management of this rare species. Here, 51 individuals in four natural populations covering the Chinese geographic range of the species were sampled to assess the genetic diversity and population structure. A total of 445,060 high-quality single nucleotide polymorphisms (SNPs) were identified using double digest restriction-site associated sequencing (ddRAD-seq). The overall average values of observed heterozygosity (Ho), expected heterozygosity (He), and average nucleotide diversity (π), were 0.2207, 0.2595, and 0.2741, respectively. The DFS-2 population exhibited the highest level of genetic diversity among all the populations. Genetic differentiation between populations was moderate (FST = 0.1425), and there was selfing between populations (FIS = 0.1390, S = 24.52%). Of the total genetic variation, 52.9% was found among populations through AMOVA analysis. The Mantel test (r = 0.982, P = 0.030) combined with analyses of the Maximum Likelihood (ML) phylogenetic tree, ADMIXTURE, and principal component analysis (PCA), revealed that populations of V. japonicum were genetically segregated and significantly correlated with their geographical distribution. Our study demonstrated that V. japonicum maintained a medium level of genetic diversity and differentiation with a strong population structure, and the results were mainly affected by its island distribution pattern and self-crossing characteristics. These results provide insights into the genetic diversity and population history of V. japonicum, critical information for conserving and sustainably developing its genetic resources.